Military adaptation in war with fear of change - Murray, Williamson 1941-2023 (Cambridge Univ. Press, 2011)
"Military Adaptation in War addresses one of the most persistent, yet rarely examined, problems that military organizations confront: namely, the problem of how to adapt under the trying, terrifying conditions of war. This work builds on the volume that Professor Williamson Murray edited with Allan Millett on military innovation (a quite different problem, though similar in some respects). In Clausewitzian terms, war is a contest, an interactive duel, which is of indeterminate length and presents a series of intractable problems at every level, from policy and strategy down to the tactical. Moreover, the fact that the enemy is adapting at the same time presents military organizations with an ever-changing set of conundrums that offer up no easy solutions. As the British general, James Wolfe, suggested before Quebec: "War is an option of difficulties." Dr. Murray provides an in-depth analysis of the problems that military forces confront in adapting to these difficulties"--
Includes bibliographical references and index
Machine generated contents note: Preface; 1. Introduction: the background to military adaptation; 2. The historical framework of adaptation; 3. Complex adaptation: the Western front 1914-1918; 4. Flawed adaptation: German adaptation and the opening battles of World War II; 5. The battle for the British Isles: June 1940-May 1941; 6. Adaptation in the air war: RAF bomber command and Luftwaffe's air defenses (15 May 1940 to 7 May 1945); 7. The 1973 Yom Kippur War; 8. Conclusion: adaptation and the future
Keywords: Strategic culture / Case studies; Tactics / Case studies; Adaptability (Psychology) / History; Military art and science / Decision making / Case studies; Operational art (Military science) / Case studies; Organizational effectiveness / Case studies; Military history, Modern / Case studies; HISTORY / Military / General; Geschichte; Strategie; Zweiter Weltkrieg; Taktik; Militär; Erster Weltkrieg; Anpassung; Jom-Kippur-Krieg; Fallstudiensammlung